Cost of near-roadway and regional air pollution-attributable childhood asthma in Los Angeles County - Brandt, Sylvia (J Allergy Clin Immunol, 2014)
BACKGROUND: Emerging evidence suggests that near-roadway air pollution (NRP) exposure causes childhood asthma. Associated costs are not well documented. OBJECTIVE: We estimated the cost of childhood asthma attributable to residential NRP exposure and regional ozone (O(3)) and nitrogen dioxide (NO(2)) in Los Angeles County. We developed a novel approach to apportion the costs between these exposures under different pollution scenarios. METHODS: We integrated results from a study of willingness to pay to reduce the burden of asthma with studies of health care utilization and charges to estimate the costs of an asthma case and exacerbation. We applied those costs to the number of asthma cases and exacerbations due to regional pollution in 2007 and to hypothetical scenarios of a 20% reduction in regional pollution in combination with a 20% reduction or increase in the proportion of the total population living within 75m of a major roadway. RESULTS: Cost of air pollution-related asthma in Los Angeles County in 2007 was $441 million for O(3) and $202 million for NO(2) in 2010 dollars. Cost of routine care (care in absence of exacerbation) accounted for 18% of the combined NRP and O(3) cost and 39% of the combined NRP and NO(2) cost—costs not recognized in previous analyses. NRP-attributable asthma accounted for 43% (O(3)) to 51% (NO(2)) of the total annual cost of exacerbations and routine care associated with pollution. Hypothetical scenarios showed that costs from increased NRP exposure may offset savings from reduced regional pollution. CONCLUSIONS: Our model disaggregates the costs of regional pollution and NRP exposure and illustrates how they might vary under alternative exposure scenarios. The cost of air pollution is a substantial burden on families and an economic loss for society.